The Wicked in Ambush (Job 27:18–19) - Pinker, Aron (Bulletin for biblical research, 2015)
Verses 18–19 have been generally understood as referring to the wicked and his demise, or the sudden loss of his wealth. The objective of this study is to clarify the image that the author tried to convey. I suggest that this image is the wicked in ambush of the innocent, a situation often referred to in the Tanach. Job claims that the wicked would not succeed in his entrapment efforts.